Evaluating Efficiency of Zakah Institutions: An Intermediation Approach Using Data Envelopment Analysis (DEA) - Rismayanti; Sepky Mardian; Mustafa Kamal; Rianti Pratiwi (International Journal of Islamic Business and Economics (IJIBEC), 2021)
This  paper  analyzes the  efficiency of Badan Aml Zakat Nasional (BAZNAS) and Dompet Dhuafa  from 2002 to 2018. Based on  selected input and output, the intermediary approach assumes that BAZNAS and Dompet Dhuafa  act  as  a link between muzakki (giver) and beneficiaries. Furthermore, BAZNAS and Dompet Dhuafa were selected  as  decision-making  units  (DMU)  from  2002  to  2018, and their efficiency  was  measured using  Data  Envelopment  Analysis  (DEA)  method  under  output-orientation with Constant Return to Sclae (CRS) and Variable Return to Scale (VRS) assumptions. The results showed both BAZNAS and Dompet Dhuafa raise the optimum efficiency in the years before 2007. Meanwhile, their inefficiency was mostly due to lack of input such as higher personalia (amil/volunteers) expenses. Therefore, these  findings  suggests  that  both  technical  and  scale efficiency should be improved  by adjusting the input. This is to achieve the most efficient and productive  level of performance in order to fulfill the institutions' objectives as an intermediary between muzakki and the beneficiaries. This paper is among the pioneers that analyzed the efficiency of zakat institutions from their initial establishment to present. Also, existing papers examined data spanning 5 years or less. Hence, long duration of data analysis provides a comprehensive evaluation of fluctuations in the zakat institutions'  efficiency and their supporting or inhibiting factors..